Romania - Functional Review : Research, Development and Innovation Sector - World Bank (Washington, DC, 2013)
A functional review by the World Bank of Romania's research, development and innovation (RD&I) sector has been commissioned by the Government of Romania and the European Commission as part of a broader assessment of the public administration contribution to the country's growth and continued convergence with the EU. The objective of the Review is to propose actions over the short to medium term to tangibly strengthen effectiveness and efficiency in the RD&I sector. This report is based on extensive literature research and data analysis, as well as three missions to Bucharest in January, March, and April 2011, during which the World Bank team met with representatives from a variety of public, private, and academic institutions and conducted a workshop with major stakeholders to review report findings. This final report -- prepared in collaboration with the World Bank Higher Education Review team and the EC's DG Research and Innovation -- presents observations and recommendations for consideration by the Government. The Review suggests that Romania's RD&I sector is in a silent crisis, with seriously negative implications for the country's longer term competitiveness and growth prospects.